2018
DOI: 10.1111/ases.12479
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative weight loss program involving a 20‐day very low‐calorie diet for obesity before laparoscopic gastrectomy for gastric cancer

Abstract: The preoperative 20-day very low-calorie diet weight loss program is promising for the treatment of obesity before laparoscopic gastrectomy for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…[ 9 ] In a similar program for obese patients with gastric cancer, a mean weight loss of 4.5%, corresponding to 3.2 kg, was reported, indicating the relative superiority of our approach. [ 10 ] In the gynecologic field, there have been no reports on weight reduction programs before surgery. Thus, to our knowledge, this is the first such study that was performed as we often treat obese women with endometrial cancer at our center.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In a similar program for obese patients with gastric cancer, a mean weight loss of 4.5%, corresponding to 3.2 kg, was reported, indicating the relative superiority of our approach. [ 10 ] In the gynecologic field, there have been no reports on weight reduction programs before surgery. Thus, to our knowledge, this is the first such study that was performed as we often treat obese women with endometrial cancer at our center.…”
Section: Discussionmentioning
confidence: 99%
“…All surgeons agreed that they would recommend implementation of this model in other facilities and that VLCD‐based treatment had positively affected surgical procedures, although this was subjective data. Three studies have previously measured surgical outcomes for patients prescribed VLCDs before non‐bariatric surgery, which showed reduced blood loss for gastrectomy ( P < 0.05) ( 38 ) , 20% shorter operating time for laparoscopic cholecystectomy ( P < 0.05) ( 23 ) and nil differences in surgical outcomes for liver resection ( 39 ) . Only one of these involved scheduled dietitian appointments (gastrectomy) and one utilised ‘explicit written dietary instructions’ provided by their surgeon (liver resection).…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al found that a very low-calorie diet preoperatively without exercise therapy reduced the body fat mass in patients with early gastric cancer. In this study, one of the daily meals (breakfast, lunch, or dinner) was changed to very low-calorie diet during preoperative 20 days [9]. However, careful consideration of this type of intervention is needed because malnutrition and sarcopenia are significant unfavorable prognostic predictors for survival in gastric cancer [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, visceral obesity is usually defined as a visceral fat area (VFA) ≥100 cm 2 measured using computed tomography (CT) [2][3][4][5][6][7]. e VFA can be reduced over a short preoperative period, unlike risk factors, such as age, sex, comorbidity, and cancer stage [8,9]. erefore, preoperative intervention for patients with high VFA may be effective for decreasing the incidence of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%